Perubahan Bid Ask Spread Di Seputar Pengumuman Laba Untuk Saham Perusahaan Manufaktur Di Bursa Efek Indonesia - Bayu Wijayantini (Benefit: Jurnal Manajemen dan Bisnis, 2016)
This study aimed to test whether there are significant non-financial variable to the bid ask spread around each earnings announcement on Manufacturing companies listed on the Indonesia Stock Exchange. The population of 143 listed company, selected 32 companies that meet the criteria. Analysis of the results showed that the analysis shows the variation change bid ask spread of 0.05. Where the average bid ask spread five days before the earnings announcement rat higher than the average bid-ask spread five days after the earnings announcement. So there are differences in the bid-ask spread significantly between the time before and the time after the earnings announcement. This indicates that most investors still regard the stock as a trade commodity. The analysis shows the variation change bid ask spread of 0.05. Where the average bid ask spread five days before the earnings announcement rat higher than the average bid-ask spread five days after the earnings announcement. So there are differences in the bid-ask spread significantly between the time before and the time after the earnings announcement. This indicates that most investors still regard the stock as a trade commodity.